Varadia, a new helicarionoidean semi-slug genus from India’s Western Ghats (Stylommatophora: Helicarionoidea) - Bhosale, Amrut R.; Saadi, Ahmed J.; Wade, Christopher M.; Thackeray, Tejas U.; Tamboli, Asif S.; Kadam, Suhas K.; Muley, Dipak V.; Raheem, Dinarzarde C. (European Journal of Taxonomy, 2021)
We here describe a new Indian helicarionoidean genus, Varadia Bhosale & Raheem gen. nov., containing the single species Varadia amboliensis Bhosale, Thackeray, Muley & Raheem gen. et sp. nov. This new semi-slug is endemic to the northern and central Western Ghats and is primarily a forest-living species. We describe and figure the shell, reproductive system, radula, spermatophore and external morphology of this new species, and detail its known distribution. We explore its relationships to other helicarionoideans using phylogenetic analyses of DNA sequence data for part of the ribosomal RNA gene cluster and discuss the morphology of the new genus in relation to other, primarily South Indian, helicarionoidean taxa. Based on characters of the reproductive system, particularly the male genitalia and the gametolytic sac, we provisionally place Varadia gen. nov. in the Macrochlamydinae (Ariophantidae). This is consistent with the results of our molecular phylogenetic analyses. The combination of large size, broad, densely tuberculated shell lobes and a shell with ca 4 whorls and a disproportionately large body whorl makes V. amboliensis gen. et sp. nov. unique among the helicarionoidean taxa of the Western Ghats. The new semi-slug is also highly distinctive in the morphology of its male genitalia.